Differences of bone quality in patients type II diabetes mellitus with mandibular cortical index analysis on panoramic radiograph - Sarifah, Norlaila; Nurrahman, Tri (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: This study aims to determine the quality of the mandibular cortex in Type II diabetes mellitus patients by analyzing the Mandibular Cortical Index on panoramic radiography. Materials and Methods: This type of research is unpaired comparative analytical design research using a cross-sectional stratified random sampling method and the Mann-Whitney statistical test. The subjects in this study were patients who visited and were diagnosed with type 2 DM for ≤ 5 years and > 5 years by doctors at the Endocrine Metabolic Internal Medicine Sub-Specialist Polyclinic, Ulin Hospital, Banjarmasin. Results: Respondents who had suffered ≤ 5 years had the highest mandibular cortical C2 index value of 10 (58.8%). Respondents who suffered > 5 years had the highest mandibular cortical C3 index value of 10 (58.8%). Diabetes mellitus patients with mandibular cortical C3 index value were ranked highest out of a total of 34 samples and were found in patients suffering from diabetes mellitus > 5 years. Conclusion: Patients with diabetes mellitus had poor bone quality, especially patients suffering from diabetes mellitus > 5 years.